#TITLE_ALTERNATIVE# - FIRDAUS (NIM: 15014093), NISQIYAH
Drainage system is one of the most important flood prevetion system in Senayan Aquatic Staidum. Flood can be caused by direct runoff on surface which will decrease absorbing of the soil. If the stadium flooding, the operational activities will be distrubed. The purpose of this final task is to design the drainage system and analyze the effectiveness of the application of absorption wells in Senayan Aquatic Stadium. Data and information used is secondary data obtained from Meteorologi Station Kemayoran. Method of the data processing using calculation manually according to rational method to calculate the rainfall and manning formula for channel discharge. After the calculation is obtained dimension of economic channel in the form of rectangular section to facilitate the work that there are three types of sizes 0,5 m x 0,7 m, 0,8 m x 0,8 m dan 1,1 m x 1,1 m. The results of the absorption well analysis are not effectively applied in large catchment areas such as Senayan Aquatic Stadium.